THE INFLUENCE OF ORGANIZATIONAL EXPERIENCE ON ENTREPRENEURIAL INTENTION THROUGH ENTREPRENEURIAL ATTITUDES IN STUDENTS FACULTY OF ECONOMICS UNIVERSITAS NEGERI MAKASSAR - Ruma, Zainal; Agus, Agus; Haslip, M. Azwar; Nurfadillah T, Rezki; Darmawinata, Widhi Nugraha Sumiharja (Universitas Negeri Makassar, 2026)
Abstract: This study aims to examine and analyze the influence of entrepreneurial literacy and organizational experience on entrepreneurial intentions through entrepreneurial attitudes in Makassar State University students. The results of this study found that organizational experience has a positive and significant effect on entrepreneurial attitudes in FE UNM students. Organizational experience has a positive and significant effect on entrepreneurial intentions in FE UNM students. Entrepreneurial attitudes have a positive and significant effect on entrepreneurial intentions in FE UNM students. Organizational experience has a positive and significant effect on entrepreneurial intentions through entrepreneurial attitudes in Makassar State University students.Keywords: Organizational Experience, Entrepreneurial Attitude, Entrepreneurial Intention